Public spending, green growth, and corruption: A local fiscal multiplier analysis for Italian provinces - Matteo Ficarra (Graduate Institute of International and Development Studies, 2024)
This paper estimates local fiscal multipliers for green and non-green public works in Italian provinces, and disentangles the geographic and institutional heterogeneities behind them. I construct a fiscal shock by taking the variation of the difference between actual and budgeted spending, and I show that it is exogenous to provincial institutional and macroeconomic conditions. Using local projections, I find that a exteuro1 increase in government spending generates negligible GDP losses in the first two years for overall and non-green projects, while it increases output by exteuro0.98 after 3 years for green projects. These results are smaller than the prevailing estimates in the literature. A triple interaction approach reveals that overall and non-green multipliers are driven by southern provinces, while the green multiplier is driven by the rest of the country, despite the contemporaneous green multiplier being equal to 1.43 in the south. I link the heterogeneity to governance characteristics: higher government effectiveness and institutional quality decrease the overall and non-green multiplier, while they increase the green multiplier. Interestingly, corruption positively affects all multipliers. I show that the effect of corruption can be explained by its role in easing bureaucratic and regulatory burdens. These results suggest that taking national fiscal multipliers at face value can lead to an overestimation of the impact of fiscal expansions.
Keywords: C33; D73; E62; H50; H72; Q43; Q58; 330; fiscal policy; local multiplier; green multiplier; climate policy; institutional quality; local projections; triple interactions